Can value chain integration explain the diverging economic performance within the EU? - Agnes Kügler; Andreas Reinstaller; Klaus S. Friesenbichler (Austrian Institute of Economic Research (WIFO), 2022)
This paper studies the interplay of integration into EU value chains and industrial development measured by labour productivity. Our integration indicator measures value chain trade within the Single Market relative to global value chain networks. Using a simultaneous equation model, we find an overall positive effect of integration on labour productivity, which is driven by upstream integration. Highly productive industries rather seek global value chain trade than regional integration, though. Better domestic institutions facilitate EU integration, although they favour industries with less complex product portfolios and lower levels of knowledge cumulativeness.
Keywords: F13; F14; O25; O43; O52; 330; EU integration; Value chains; Productivity; Institutions; Industrial development; Product complexity